2018
DOI: 10.1172/jci91921
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent hypoglycemia inhibits the counterregulatory response by suppressing adrenal activity

Abstract: Hypoglycemia activates the counterregulatory response (CRR), a neural-endocrine reflex that restores euglycemia. Although effective if occasionally activated, repeated induction of the CRR leads to a decline in responsiveness and prolonged exposure to hypoglycemia. The mechanism underlying this impairment is not known. We found that the reduction in epinephrine release that characterizes a suppressed CRR involves a long-lasting form of sympatho-adrenal synaptic plasticity. Using optogenetically evoked catechol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…The development of a peripheral defect at the level of epinephrine-secreting chromaffin cells after recurrent hypoglycemia contributes to the impaired counterregulatory secretion of epinephrine (28, 38). Ma et al (28) showed that in a rodent model of HAAF defects existed in the adrenal gland but not in the downstream hepatic components of the counterregulatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of a peripheral defect at the level of epinephrine-secreting chromaffin cells after recurrent hypoglycemia contributes to the impaired counterregulatory secretion of epinephrine (28, 38). Ma et al (28) showed that in a rodent model of HAAF defects existed in the adrenal gland but not in the downstream hepatic components of the counterregulatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a peripheral defect at the level of epinephrine-secreting chromaffin cells after recurrent hypoglycemia contributes to the impaired counterregulatory secretion of epinephrine (28, 38). Ma et al (28) showed that in a rodent model of HAAF defects existed in the adrenal gland but not in the downstream hepatic components of the counterregulatory response. These results suggest that impaired sympathetic efferent neuronal signaling causes reduced activation of epinephrine-secreting cells in the adrenal gland, since cell death was not observed in the adrenal gland (28).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive compensation of brain glycogen levels during recurrent hypoglycemia could contribute to the development of hypoglycemia-associated autonomic failure in humans (15). Inhibition of the counterregulatory response by suppressed adrenal activity has been observed in animal models (16).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the sympatho-adrenal system, facilitation may have a role in amplifying epinephrine discharge from chromaffin cells during conditions that increase sympathetic tone, including hypoglycemia (13,53). The resulting increase in circulating epinephrine would then be expected to increase blood glucose via multiple metabolic pathways (13,53,54). Our data show that in Syt7 KO animals fed ad libitum, epinephrine content in the adrenal medulla, as well as in the blood, are not different from WT animals ( Figure 6).…”
Section: Discussionmentioning
confidence: 99%